Dziedzictwo Ojców pustyni w "Regule" św. Benedykta - Borkowska, Małgorzata (Vox Patrum, 1997)
The teachings of the Desert Fathers are for St. Benedict the primary source of monastic tradition. He does not, however, draw from this source indiscriminately. In every point on which the tradition is divided into different schools he makes a decided choice between them; often, by the way, a different choice than that made by his chief textual source, the Regula Magistri. Since his choices were to influence the whole history and spirituality of the Western monasticism, it is important to realize the lines on which they were made, even if they seem (after 15 centuries) matter of course.